1994
DOI: 10.1093/oxfordjournals.bmb.a072887
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous disease and alcohol misuse

Abstract: Certain skin disorders have now been demonstrated to be affected by alcohol misuse, in particular psoriasis and discoid eczema. The pattern of involvement in psoriasis differs from psoriasis vulgaris in character and distribution, and tends to be more difficult to treat. Discoid eczema appears to be specifically related to alcohol excess and is associated with deranged liver function tests. Rosacea, post-adolescent acne, superficial infections and porphyria cutanea tarda may also be markers of alcohol misuse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 0 publications
4
57
1
6
Order By: Relevance
“…Drinking is a recognised stress response and it has been argued that alcohol misuse is a consequence of the stress, rather than being causally related. 9,10 Examination of the temporal relationship between alcohol misuse and the onset of disorder, shows that it is alcohol which provokes psoriasis. Abstinence has been observed to produce clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking is a recognised stress response and it has been argued that alcohol misuse is a consequence of the stress, rather than being causally related. 9,10 Examination of the temporal relationship between alcohol misuse and the onset of disorder, shows that it is alcohol which provokes psoriasis. Abstinence has been observed to produce clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Abstinence has been observed to produce clinical improvement. 9 Thus, to conclude, alcoholism is a social disease with wide ramifications. The dermatoses in alcohol dependant patients are varied.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has documented psychological intervention for a number of cutanoeus conditions such as vitiligo, psoriasis, acne vulgaris and, atopic dermatitis, which have been suggested to be as effective for each of these types of disorder as classical medical therapeutic process (Van Moffaert, 1992;Higgins & Du Viver, 1994). In our study we found positive correlation between psychological intervention (psychoanalytical psychotherapy and cognitive behavioural therapy) and dermatological disorders such as acne vulgaris, atopic dermatitis, lichen planus, psoriasis, chronic urticaria and viral infections which includes facial/genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, there was an 18% prevalence of alcoholism in patients with psoriasis compared to 2% among dermatologic controls [60]. Several studies have shown that treatment outcomes are worse in heavy drinkers [62][63][64]. Abstinence alone has been shown to possibly induce psoriasis remission, whereas restarting drinking may cause disease relapse [62,65].…”
Section: Psoriatic Arthritismentioning
confidence: 99%